TUMB at the SBFT 2024 Tool Competition - CPS-UAV Test Case Generation Track - Tang, Shuncheng; Zhang, Zhenya; Cetinkaya, Ahmet; Arcaini, Paolo (2024 IEEE/ACM International Workshop on Search-Based and Fuzz Testing (SBFT), 2024)
TUMB is a generator of scenarios for UAV testing, that participated in the UAV Testing Competition at SBFT 2024. TUMB relies on Monte Carlo Tree Search (MCTS) to search for different placements of obstacles of different sizes in the mission environment. Increasing the tree depth corresponds to adding a new obstacle to the environment, while adding a new node in the current tree level corresponds to the optimisation of the placement and of the dimension of the last added obstacle.